Eventos patológicos em placenta e soro de cabras naturalmente infectadaspor Neospora caninum - Orlando, Débora Ribeiro (2017)
During gestation, females develop a type Th2 immunological response. However, when infection or resurgence of infectious agents occur, a polarization for type Th1 immune response can limit the multiplication of the parasite, yet it is related to abortion. A resurgence of the chronic infection can occur during the gestation of ruminants, and its causes are still unknown. The objective of this work was to evaluate parameters of immune response during natural chronic infection by Neospora caninum in pregnant goats. Thus, serum cytokines (IL-4, IL-10, IL-12, IFNɣ and TNF-α) were quantified by ELISA technique, on nine animals (seven of them positive to N. caninum). Immunostaining for T lymphocytes, auxiliary T lymphocytes, B lymphocytes, Tgamma delta, Natural Killer, macrophages, IFNɣ and MHC-II were done on the maternal-fetus placental interface. The data regarding the cell count of the goats with different titers for Neospora caninum were submitted to the Kruskal-Wallis test (p<0.05). Reacting and non-reacting goats present variations in the production of cytokines during the five months of gestation. Only one goat presented cotyledons with irregular and swollen edges, chorioallantoic membrane with edema near the cotyledons and multifocal petechiae. Microscopically, the most frequent lesions were discrete multifocal lymphoplasmacytic infiltrate in the trophoblastic mesenchyme, necrosis areas in the chorionic epithelium, multifocal mineralization and discrete multifocal lymphohistioplasmacitary infiltrate in the uterine submucosa. Only in one goat, many N. caninum cysts were seen. There was statistical difference between the number of cells marked by the immunohistochemistry in positive animals when compared to negative animals. Thus, a differentiated immunological response occurs for positive and negative animals, yet, not always, does the abortion occur.